入世与中国三鹿乳业集团 ： 影响及对策 = WTO and China's SANLU Dairy Group : impacts and solutions - 葛瑞芳 Ge, Rui Fang (2008)
This thesis starts with an analysis of both internal strength and external environment, using the relevant economic principles and the theory of competitive advantages.